Kinerja Aparatur Dalam Pelayanan Administrasi Kependudukan Di Kantor Kecamatan Kapala Pitu Kabupaten Toraja Utara - Viny Marsela Sombodatu; Nasir Mangasing (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research was conducted at the Kapala Pitu Sub-District Office, North Toraja Regency, with the aim of determining the